2017
DOI: 10.1002/jbm.a.35990
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a calcium carbonate‐based bone substitute with cinnamaldehyde crosslinking agent with potential anti‐inflammatory properties

Abstract: Calcium sulfate (CS), also known as POP (Plaster of Paris) is a self-setting, biocompatible, and osteoconductive biomaterial with a long history for the treatment of skeletal defects. However, CS cements show a too fast resorption rate and are unable to provide a long-term 3D framework during the osteogenesis process. In our previous studies, it was found that the incorporation of CaCO and CaCO hydrogel provided enhanced mechanical and degradation properties of POP composites. Furthermore, it was also found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…All the hydrogels showed biphasic release profiles, with fast initial release (up to 180 min), followed by sustained release. Similar results have been reported in other studies employing polymeric systems containing natural compounds. For hydrogels containing nanoparticulate systems, faster release in the early stages is associated with the nonencapsulated or nonadsorbed compound present on the particle surface. For hydrogels containing emulsions, the release is faster, due to the high availability of the active compounds.…”
Section: Resultssupporting
confidence: 85%
“…All the hydrogels showed biphasic release profiles, with fast initial release (up to 180 min), followed by sustained release. Similar results have been reported in other studies employing polymeric systems containing natural compounds. For hydrogels containing nanoparticulate systems, faster release in the early stages is associated with the nonencapsulated or nonadsorbed compound present on the particle surface. For hydrogels containing emulsions, the release is faster, due to the high availability of the active compounds.…”
Section: Resultssupporting
confidence: 85%
“…Cinnamaldehyde or cinnamic aldehyde (3-phenyl-2-propenal) is the main component in cassia oil and cinnamon bark oil. 19 Cinnamaldehyde is a chemical ingredient of cinnamon that has antiinflammatory, 5,6 anti-bacterial, 4 and osteogenic properties. 15 Gypsum-based artificial bone scaffolding and calcium carbonate hydrogel have been shown to increase osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It revealed that increasing the crosslinking degree reduced swelling ratios of the hydrogels, which was consistent with previous reports. 14,15 This could be explained that with the increase of the crosslinking degrees, there would be more coupling between amine groups and carboxyl groups, which resulted in more covalent bonds among the copolypeptide chains and nally made the hydrogels hard to swell.…”
Section: Preparation and Characterization Of Hydrogelsmentioning
confidence: 99%